Atypical occupational statuses: equal opportunities or discrimination? - Ghebrea, Georgeta (Calitatea Vieții, 2016)
The present paper is a preliminary analysis on multiplication and diversification of employment. We intend to investigate several issues of atypical employment: explanatory factors of the emergence and development of atypical employment; inventory of atypical occupational statuses; socio-demographic and psychological profile of atypical workers; benefits and risks of atypical occupational statuses; main policies of equal opportunity between regular and atypical occupational statuses in the European Union and Romania. The results of this analysis showed that most atypical workers are, in terms of age and gender, young people and/or women; for them, the disadvantages of atypical employment outweigh the benefits and the risk of discrimination is quite high; this risk suggests an insufficient adjustment of existing social policies to the specificity and diversity of atypical employment. In Romania, atypical employment is often a survival strategy for people who cannot accede to a regular occupational status. Even if, theoretically, 90% of Romanian atypical workers are covered by the social security systems, such data are ignoring an important category, namely, informal employment.